Missing a lot of this world : formal education and political competition in Iraq through a Yezidi lens - Wadsworth, Daria (2017)
This thesis examines Yezidi perceptions of access to formal education for Yezidi children and youth from the Sinjar region of Iraq, a primary homeland of the Yezidi people and an officially disputed territory between the Kurdistan Regional Government (KRG) and the federal government of Iraq in Baghdad, between the periods of 2003–2014 and 2014 onwards. These two time frames are selected and differentiated to reflect two major events in the recent history of Sinjar – the downfall of Saddam Hussein’s regime in 2003 and subsequent de facto control of Sinjar by the KRG, and the seizing of the area by the Islamic State (IS) group and subsequent displacement of the majority of the Yezidi community in 2014. This thesis also seeks to understand prominent Yezidi discourses around this issue and the implications for Yezidi children and youth from Sinjar, and for the Yezidi community as a whole.